Extracellular polysaccharide-facilitated selenium nanoparticle assembly and metabolic reprogramming support efficient selenite biotransformation by ARTP-mutagenized Lactiplantibacillus plantarum Vse252 - Lihui Tan; Xinyan Wang; Lin Hu; Xiang Gen; Shirui Yu; Xue Li; Xinyu Yan; Bo He; Jun Zhang; Yongzhong Wang; Hengqian Lu (Bioresource Technology, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Uplift capacity of suction anchor groups for floating offshore wind turbines: Loading-angle and mooring-position effects - Yancheng Yu; Xuanming Ding; Yu Peng; Jinchuan Wang; Gen Xiong; Ben He; Yiwen Xin (Marine Georesources & Geotechnology, 2026)

Activation of mTOR signaling improves nutrient utilization in pacific white shrimp (Litopenaeus vannamei) fed low-fishmeal diets replaced by composite plant protein sources - Yawen Shu; Huihui Zhou; Xuan Wang; Chengdong Liu; Kangsen Mai; Gen He (Aquaculture, 2026)

Power-Load Characteristics of Fixed Oscillating Water Column Chambers for Potential Integration with Offshore Wind Jacket Foundations - Guohu Xie; Qinzhang Li; Fangyuan Yi; Rongquan Wang; Gen Xiong; Dezhi Ning; Ben He (Journal of Marine Science and Engineering, 2026)
The integration of wave energy converters with offshore wind foundations offers a potential route to improving the utilization of offshore renewable energy infrastructure. This study numerically investigates the power-load characteristics of fixed oscillating water column (OWC) chambers intended for potential installation near offshore wind jacket foundations. A preliminary jacket comparison is first used to delimit the scope, after which the main parametric study is performed on isolated OWC chambers so that pneumatic response and local chamber loads can be compared consistently. The simulations are conducted under regular waves with a wave height of H = 0.05 m, a water depth of h = 1.6 m, and wave periods of T = 0.9–1.7 s. Three baseline geometries, namely cylindrical, sandglass-shaped, and bottle-shaped OWCs, are first screened in order to identify the most suitable reference chamber family. The cylindrical chamber is then retained as the reference configuration for subsequent local parameter studies of the frustum-contraction parameter D2 and the front-wall draft d2. The results indicate that the geometric effect is strongly dependent on the incident-wave period. The sandglass-shaped and bottle-shaped chambers can enhance short-period pneumatic power or reduce loads at longer periods, whereas the cylindrical chamber provides a more consistent reference response over the tested range. Under the wave conditions adopted in this study, further analysis reveals that D2 exerts a non-monotonic tuning effect varying with wave period. For the selected frustum-shaped configuration, increasing d2 reduces hydrodynamic loads yet simultaneously weakens pneumatic power output and CWR. Because the air phase is treated as incompressible and the orifice represents an orifice-only damping condition rather than a turbine-controlled PTO system, the reported Pe should be interpreted as a pneumatic/hydrodynamic comparison metric and not as wave-to-wire electrical power. The conclusions are therefore positioned as regular-wave geometry-tuning trends for the present model scale rather than as full coupled jacket-OWC design rules.

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Adipose tissue-secreted Igf2 during promoting adipocyte hyperplasia improves muscle texture caused by high-fat diet through inhibiting myostatin in grass carp (Ctenopharyngodon idellus) - Zhiqi Tian; Handong Li; Mingkui Wei; Hong Ji; Gen He; Jian Sun (Aquaculture, 2026)

High-fidelity aero-elastic decoupling approach for dynamic response analysis of offshore wind turbines - Yongqing Lai; Ben He; Gen Xiong; Renqiang Xi; M. Hesham El Naggar (Soil Dynamics and Earthquake Engineering, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Research on Fracture Characteristics and Crack Propagation Patterns of Freeze-Thaw Damaged Rock Under Loading - Ding Ma; Mei-lu Yu; Lin-kai He; Zhong-wen Wang; Zi-yi Yang; Gen-shui Wu (Applied Geophysics, 2026)

Study on acoustic elasticity of vibrating liquid column used for hydrophone calibration - Limu Qin; Jie Zhou; Gen Zhang; Yue Xu; Chenhao Wu; Wen He (Wave Motion, 2026)

Detecting and comparing extinction debts of amphibians in China under climate change - Yu-Xiao He; You-Hua Chen; Xiao-Qin Shi; Chao-Sheng Mu; Dan-Dan Yu; Jia-Qi Li; Hai-Gen Xu; Jian-Ping Jiang (Biological Conservation, 2026)

Analysis of the morphodynamic characteristics of macrotidal beaches on the western coast of the Taiwan Strait - Yanqing Wei; Hongshuai Qi; Gen Liu; Feng Cai; Yanyu He; Kaiqi Hua; Shaohua Zhao (Regional Studies in Marine Science, 2025)

Numerical Simulation and Tests of Lateral Bearing Capacity of Sloped Offshore Monopile Under Vertical Load and Lateral Cyclic Load - Yongqing Lai; Gen Xiong; Ben He; Yilong Sun; Lin Guo; Kaiyuan Liu (Journal of Marine Science and Engineering, 2025)
Offshore monopile foundations endure complex loads during service. They bear vertical loads from the superstructure’s self-weight and lateral cyclic loads (e.g., wind, waves), while near-coastal seabeds are usually sloped. To resolve these issues, model pile tests under combined vertical and lateral cyclic loads were carried out to study how slope angle and vertical load affect monopile deformation. A numerical model was validated via comparison with test results and then used to reveal the development of cumulative deformation in offshore sloped monopiles under the above combined loads. The results show that, below 1000 cycles, the cumulative displacement of the pile increases logarithmically with the number of cycles. As the slope angle increases, the cumulative deformation increases. In these tests, the cumulative deformation of the pile increases by 114% compared to the results of the flat site, but it decreases with an increase in vertical load. As such, when a 3 N vertical load is applied to the pile top, its deformation at the flat site decreases by 20%, but its deformation at a 20° slope site decreases by 10%. Finally, a predicted formula is proposed for offshore monopiles with the effect of slope angle, and this formula can provide a preliminary assessment method of cumulative.

Carbon emission reduction potential of on-demand transit replacing fixed-route transit - Xiao-Fan Wei; Zhe Zhang; Zhong-Ren Peng; Mei-Gen Xue; Hong-Di He (Transportation Research Part D: Transport and Environment, 2025)

A framework to mitigate aeolian erosion on nourished beaches - Yanyu He; Feng Cai; Jianhui Liu; Hongshuai Qi; Bailiang Li; Chao Cao; Shaohua Zhao; Gen Liu; Xu Chen; Jiaqi Huang (Coastal Engineering, 2025)

Oxidative stress and metabolic perturbations unravel the molecular basis of high dietary poultry by-product meal-induced growth impairment and inflammation response in Litopenaeus vannamei - Chenxi Wang; Huali Feng; Jican Zhao; Chengdong Liu; Xuan Wang; Huihui Zhou; Kangsen Mai; Gen He (Fish & Shellfish Immunology, 2025)

Administration of EPA improves lipopolysaccharide-induced intestinal dysfunction in turbot (Scophthalmus maximus L.) through modulation of TORC1 signaling - Zongyu Gao; Ya Gao; Xuan Wang; Tingting Wang; Huihui Zhou; Chengdong Liu; Kangsen Mai; Gen He (Fish & Shellfish Immunology, 2025)

Impacts of endosymbionts on fitness parameters of hemipteran insects: a Meta-analysis - Junming Li; Gen Zhou; Wenze He; Jianyu Deng; Xunyue Liu; Qiong Rao (Symbiosis, 2025)

Temperature regulated nutrient sensing and metabolism of amino acids in juvenile turbot (Scophthalmus maximus L.) - Xuemin Zhang; Jiru Wang; Chengdong Liu; Xuan Wang; Huihui Zhou; Kangsen Mai; Gen He (Marine Life Science & Technology, 2025)
Temperature is well known as the major environmental factor that influences survival and growth of fish, which are poikilothermic animals. However, it is still unclear about the mechanism that underscores thermal-controlled fish physiology, especially nutritional utilization and metabolism, which are vitally important in aquaculture. In the present study, juvenile turbot was force-fed with amino acid mixture and its postprandial absorption, nutrient sensing and metabolism under low (12, 15 ℃), optimal (18 ℃) to high (21, 24 ℃) temperatures were explored. Intestinal trypsin and lipase activity were highly sensitive to water temperature, and highest under optimal temperatures for turbot, whereas amylase remained constant. Selective groups of intestinal amino acid transporters were upregulated in cold temperatures, but the amino acid absorption capability was increased with rising temperature. The mechanistic target of rapamycin (mTOR) signaling pathway was most active at optimal temperature. Postprandial muscle protein deposition achieved maximum level under optimal temperature. Amino acid catabolic enzymes branched-chain aminotransferase and branched-chain α-keto acid dehydrogenase activities were increased with rising temperatures. High temperature increased significantly energy metabolism and stimulated cellular stress in liver. These findings highlight the critical role of temperature in modulating amino acid dynamics, metabolic processes and stress responses in juvenile turbot, providing valuable insights for optimizing aquaculture practices.

Porcine epidemic diarrhea virus induces mitophagy to inhibit the apoptosis and activation of JAK/STAT1 pathway - Xin Li; Yiwan Wu; Jin Peng; Bingjie Li; XiaoLong Li; Zhibin Yan; Gen Li; Yue Zhang; HongLing He; Jun Luo; Xiaofeng Guo (Veterinary Microbiology, 2025)

Promoting adipocyte hyperplasia ameliorates high-carbohydrate diet-induced inflammation, oxidative stress, and metabolic disorders and enhances growth performance and immune function in grass carp (Ctenopharyngodon idellus) - Mingkui Wei; Zhiqi Tian; Niankun Zhang; Lu Zhou; Handong Li; Hong Ji; Gen He; Jianlu Zhang; Jian Sun (Fish Physiology and Biochemistry, 2025)

Lake level variability on the Northeastern Tibetan Plateau linked to interaction between Westerlies and Asian monsoon since the last deglaciation - Xueyun Ma; Zhifu Wei; Gen Wang; Ting Zhang; Pengyuan Zhang; Kaikang Liang; Zengguang Guo; Shangkun Li; Xiaomei Zhang; Jianzhen Chen; Zelong Li; Wei He; et al. (CATENA, 2025)

Metabolomics-based mechanistic insights into antioxidant enhancement in mango juice fermented by various lactic acid bacteria - Shuai Liu; Yu-Jia Peng; Wei-Wei He; Xiao-Xiao Song; Yu-Xin He; Xiao-Yi Hu; Shui-Gen Bian; Yu-Hao Li; Jun-Yi Yin; Shao-Ping Nie; Ming-Yong Xie (Food Chemistry, 2025)

Innovative coupling pathway for second- and third-generation biomass: Efficient L-lactate synthesis from xylose and C1 compounds - Ya Wu; Gen Lu; Ruiqi Zeng; Zeyang Li; Xin Xu; Yifan Gui; Chonghao Guo; Lizhen Deng; Yutong Bie; Derui Zhang; Yuxin He; Yuyang He; et al. (Chemical Engineering Journal, 2025)

Improved viability of probiotics by co-encapsulation of wheat germ oil under storage and gastrointestinal conditions: Effects of drying methods and wall composition - Bao-Lin He; Rui Cui; Teng-Gen Hu; Hong Wu (Food Hydrocolloids, 2025)

Assessing the Interrelationship Between Microplastics and Polychlorinated Biphenyls Contamination in Chinese Mangrove Sediment - Jianqiao He; Jun Deng; Guochao Zhang; Guoqiang Yi; Gen Peng; Yihua Wei; Lu Ren; Yinghui Wang (Journal of Marine Science and Engineering, 2024)
Mangrove ecosystems, critical intertidal zones at the land–ocean interface, are increasingly recognized for their role in microplastic (MP) pollution dynamics. Despite extensive research on the interaction of MPs with various chemical contaminants, the specific contamination levels of polychlorinated biphenyls (PCBs) associated with MPs in mangroves remain poorly understood. In this study, we quantified the concentrations of PCBs on MPs extracted from representative mangrove sediment samples across China, revealing values ranging from 9.80 to 13.91 ng/g. In contrast, PCB concentrations in sediment samples were found to vary between 25.67 and 69.85 ng/g. Our findings indicate a consistent level of PCB contamination on MPs across different sites, although these levels were marginally elevated compared to those in the surrounding sediments. Notably, Penta-PCBs were detected with the highest frequency across all samples analyzed. This study provides crucial insights into the occurrence and distribution of PCBs on MPs within the mangrove ecosystem, highlighting their significance in environmental contamination assessments.

Purification of asparagus canning wastewater by combined membrane technology and recovery kinetics of saponins - Tianyu Kong; Xiaoxi Zhang; Yinfei Ma; Xinhuan Yan; Gen Li; Xiaodan Zhao; Fatao He; Maoyu Wu; Enjuan Shi; Yan Zhao; Le Chu (Journal of Water Process Engineering, 2024)

Distinctive patterns of bacterial community succession in the riverine micro-plastisphere in view of biofilm development and ecological niches - Zhen Zhao; Yijin Wang; Yihua Wei; Gen Peng; Tingyu Wei; Jianqiao He; Ruilong Li; Yinghui Wang (Journal of Hazardous Materials, 2024)

Peteryoungia algae sp. nov. isolated from seaweeds of Gouqi Island, China, and its unique genetic features among Peteryoungia strains - Jun Yin; Min He; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Gen Chen; Ze-Fei Wang; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Antonie van Leeuwenhoek, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Characterization and Genomic Analysis of Affinirhizobium gouqiense sp. nov. Isolated from Seawater of Gouqi Island Located in the East China Sea and Reclassification of Rhizobium lemnae to the Genus Affinirhizobium as Affinirhizobium lemnae comb. nov. - Min He; Gen Chen; Ke-Jing Li; Xing-Xing Tang; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Current Microbiology, 2024)

Loss of Gcn2 exacerbates gossypol induced oxidative stress, apoptosis and inflammation in zebrafish - Mingjun Tang; Weiyi Xia; Fei Song; Chengdong Liu; Xuan Wang; Huihui Zhou; Kangsen Mai; Gen He (Fish & Shellfish Immunology, 2024)

EPA and DHA promote cell proliferation and enhance activity of the Akt-TOR-S6K anabolic signaling pathway in primary muscle cells of turbot (Scophthalmus maximus L.) - Ya Gao; Chengdong Liu; Xuan Wang; Huihui Zhou; Kangsen Mai; Gen He (Fish Physiology and Biochemistry, 2024)

Decadal evolution of a sandy beach adjacent to a river mouth under natural drivers and human impacts - Gen Liu; Feng Cai; Hongshuai Qi; Jianhui Liu; Chao Cao; Shaohua Zhao; Yanyu He; Jun Zhu; Chao Yin; Wenyuan Mo (Frontiers in Marine Science, 2024)
As escalating environmental pressures threaten the world’s beaches, understanding the driving factors influencing their geomorphological changes is of critical global importance. This study focuses on the morphological changes of Sigeng beach adjacent to Changhua River Mouth in Hainan Island, China through decadal monitoring of shoreline and profile topography and tries to illuminate the natural and anthropogenic factors that drove geomorphological changes. The results showed that Sigeng beach undergone significant changes between 2008 and 2024, with notable accretion at the northernmost and southernmost and general erosion at other sections. The shoreline change rates ranged between -18.4 m/yr and 13.0 m/yr, with the average rate of -1.9 m/yr, indicating overall erosion. The net longshore sediment transport (LST) rates along Sigeng beach was estimated through the combination of the cross-shore (profile) and longshore (shoreline) changes. The overall direction of net LST along the beach were southward, except for the northern section where the direction was northward due to the diffraction of NE waves by the long sand spit at the northernmost. The net LST rates at each profile varied from 0.8×10 4 m 3 /yr to 3.5×10 4 m 3 /yr. The main factors controlling Sigeng beach evolution, including seasonal wave action and reduction in fluvial sediment load, followed by sand spit and coastal structures, typhoon events, aeolian transport, and sea level rise, were discussed. Subsequently, adaptive protection measures, including beach nourishment, accompanied with groin system or multiple detached breakwaters were proposed to combat with beach erosion. The analysis presented in this study is helpful to understand the morphodynamics and to predict the future change of beaches.

Research on the influence of panel zone on dynamic damage of multi-story steel structure - Zhong-gen Xu; Ya-tao Zhao; Hao-jie Wu; En-he Bao (European Journal of Environmental and Civil Engineering, 2024)

Methionine deficiency affects myogenesis and muscle macronutrient metabolism in juvenile turbot Scophthalmus maximus - Zhongmin Sui; Xuan Wang; Yongkai Sun; Huihui Zhou; Chengdong Liu; Kangsen Mai; Gen He (Aquaculture, 2024)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

A benchmark study for quasi-static numerical upscaling of seismic wave attenuation and dispersion in fractured poroelastic rocks - Meng-Fan Zhang; Yan-Xiao He; Shang-Xu Wang; Gen-Yang Tang; Chao Sun (Computers & Geosciences, 2023)

Influence of Blade Flexibility on the Dynamic Behaviors of Monopile-Supported Offshore Wind Turbines - Yongqing Lai; Wei Li; Ben He; Gen Xiong; Renqiang Xi; Piguang Wang (Journal of Marine Science and Engineering, 2023)
At present, monopile-supported offshore wind turbines (MOWTs) are widely used in offshore wind farms. The influence of blade flexibility on the dynamic behaviors of MOWTs excited by waves and earthquakes was investigated in this study. Numerical analysis models were established for 5 MW and 10 MW MOWTs, incorporating flexible and rigid blade configurations. The modes and natural frequencies of the full system were compared between these two numerical models, and their dynamic responses were evaluated under wave-only and earthquake-only excitations. It was revealed that the influence of blade flexibility on the first- and second-order modes of the system can be neglected. The dynamic response of these MOWTs under wave excitation can be predicted by the rigid blade model, where the maximum relative difference is less than 5%. However, higher-order modes of the system are significantly affected by the blade flexibility. Under high-frequency excitations, these higher-order modes of the system are remarkably stimulated. Additionally, a large relative difference, exceeding 50%, is detected when the rigid blade model is used to predict the seismic response of the two MOWTs. Consequently, the blade flexibility should be adequately modeled when predicting the dynamic response of OWTs.

Bifidobacterium spp. as functional foods: A review of current status, challenges, and strategies - Bao-Lin He; Yong Xiong; Teng-Gen Hu; Min-Hua Zong; Hong Wu (Critical Reviews in Food Science and Nutrition, 2023)

Dynamic process and dynamic-stall phenomenon on blade sections of a floating horizontal-axis wind turbine caused by the platform's pitch motion - Zanyang He; Gen Li; Lei Duan; Qinghong Sun (Ocean Engineering, 2023)

Phenotypic screening of novel probiotics with potential anti-neuroinflammation activity based on cell and zebrafish models - Bao-Lin He; Teng-Gen Hu; Hong Wu (Food Bioscience, 2023)

Effects of dietary chloroquine on fish growth, hepatic intermediary metabolism, antioxidant and inflammatory responses in turbot - Zhongmin Sui; Xuan Wang; Xiaojing Zhang; Huihui Zhou; Chengdong Liu; Kangsen Mai; Gen He (Fish & Shellfish Immunology, 2023)

Comprehensive study on the effect of dietary leucine supplementation on intestinal physiology, TOR signaling and microbiota in juvenile turbot (Scophthalmus maximus L.) - Zhongmin Sui; Ning Wang; Xiaojing Zhang; Chengdong Liu; Xuan Wang; Huihui Zhou; Kangsen Mai; Gen He (Fish & Shellfish Immunology, 2023)

Drought shifts soil nematodes to smaller size across biological scales - Leilei Lu; Gen Li; Nianpeng He; Huixin Li; Ting Liu; Xianping Li; Joann K. Whalen; Stefan Geisen; Manqiang Liu (Soil Biology and Biochemistry, 2023)

Three-Dimensional Prescribed Performance Tracking Control of UUV via PMPC and RBFNN-FTTSMC - Jiawei Li; Yingkai Xia; Gen Xu; Zixuan He; Kan Xu; Guohua Xu (Journal of Marine Science and Engineering, 2023)
To address the search-and-docking problem in multi-stage prescribed performance switching (MPPS) scenarios, this paper presents a novel compound control method for three-dimensional (3D) underwater trajectory tracking control of unmanned underwater vehicles (UUVs) subjected to unknown disturbances. The proposed control framework can be divided into two parts: kinematics control and dynamics control. In the kinematics control loop, a novel parallel model predictive control (PMPC) law is proposed, which is composed of a soft-constrained model predictive controller (SMPC) and hard-constrained model predictive controller (HMPC), and utilizes a weight allocator to enable switching between soft and hard constraints based on task goals, thus achieving global optimal control in MPPS scenarios. In the dynamics control loop, a finite-time terminal sliding mode control (FTTSMC) method combining a finite-time radial basis function neural network adaptive disturbance observer (RBFNN-FTTSMC) is proposed to achieve disturbance estimation and fast convergence of velocity tracking errors. The simulation results demonstrate that the proposed PMPC-FTTSMC approach achieved an average improvement of 33% and 80% in the number of iterations compared with MPC with sliding mode control (MPC-SMC) and traditional MPC methods, respectively. Furthermore, the approach improved the speed of response by 35% and 44%, respectively, while accurately achieving disturbance observation and enhancing the system robustness.

Long-term drying trends since the mid-Holocene in the Qaidam Basin - Ting Zhang; Gen Wang; Yongli Wang; Zhifu Wei; Wei He; Xueyun Ma; He Ma; Xiaoli Yu; Pengyuan Zhang; Shangkun Li; Jingyi Wei; Lun Li (CATENA, 2023)

Variation in cross-shore wind speeds influenced by the morphology of nourished beach - Xu Chen; Jianhui Liu; Feng Cai; Yanyu He; Bailiang Li; Hongshuai Qi; Shaohua Zhao; Gen Liu (Acta Oceanologica Sinica, 2023)

A novel photochemical conversion technique for reliable calibration of peroxyacetyl nitrate (PAN) analyzers - Xiaowei He; Chenglong Zhang; Pengfei Liu; Gen Zhang; Hai Wu; Yuexiang Peng; Junfeng Liu; Chengtang Liu; Yujing Mu (Science of The Total Environment, 2023)

Links between geochemical weathering on the NE Tibetan Plateau and global climate change since the Last Deglacial - Xueyun Ma; Zhifu Wei; Yongli Wang; Gen Wang; Ting Zhang; Wei He; Xiaoli Yu; He Ma; Pengyuan Zhang; Shangkun Li; Qiaohui Fan (CATENA, 2023)

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Optimal dietary methionine requirement of sub-adult turbot (Scophthalmus maximus L.): Growth performance, feed utilization and hepatic lipid metabolism - Zhongmin Sui; Xuan Wang; Yongkai Sun; Huihui Zhou; Chengdong Liu; Kangsen Mai; Gen He (Aquaculture, 2023)

Correction to: Preliminary analyses of the Tiejiangwan landslide occurred on April 5, 2021 in Hongya County, Sichuan Province, China - Bo Liu; Xiewen Hu; Kun He; Gen Li; Xin Liu; Gang Luo; Chuanjie Xi; Ruichen Zhou (Landslides, 2022)

Preliminary analyses of the Tiejiangwan landslide occurred on April 5, 2021 in Hongya County, Sichuan Province, China - Bo Liu; Xiewen Hu; Kun He; Gen Li; Xin Liu; Gang Luo; Chuanjie Xi; Ruichen Zhou (Landslides, 2022)

Dietary lysine level affects digestive enzyme, amino acid transport and hepatic intermediary metabolism in turbot (Scophthalmus maximus) - Xinrui Huang; Xinxin Song; Xuan Wang; Huihui Zhou; Chengdong Liu; Kangsen Mai; Gen He (Fish Physiology and Biochemistry, 2022)

Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α -glucosidase inhibitory activity - Min Song; Tong Xiao; Qiu-Shuang Wu; Hang Fai Kwok; Ging Chan; Li-Gen Lin; Xiao-Qi Zhang; Wen-Cai Ye; Sheng-Jiang He; Qing-Wen Zhang (Natural Product Research, 2022)

Distribution of n ‐alkan‐2‐ones in Qionghai Lake sediments, southwest China, and its potential for late Quaternary paleoclimate reconstruction - Gen Wang; Yongli Wang; Zhifu Wei; Wei He; Ting Zhang; Xueyun Ma; Xiaoli Yu (Journal of Quaternary Science, 2021)
Studies on long‐chain n ‐alkan‐2‐ones from lake sediments remain sparse. In this study, we present an n ‐alkan‐2‐one record from Qionghai Lake, southwest China, to assess the paleoclimate significance of variations in their compositions. A homologous series of n ‐alkan‐2‐ones ranging from C 21 to C 35 were identified, with maximum concentrations of the C 29 or C 31 chain lengths and a strong odd‐over‐even predominance. This type of n ‐alkan‐2‐one is considered to derive mainly from microbial oxidation of the corresponding n ‐alkanes, and partial inputs from plants. The n ‐alkan‐2‐one‐derived average chain length (ACL) and carbon preference index (CPI) values changed significantly over the past 28k cal a bp , consistent with the sediment grain size and n ‐alkane proxies from the same core. Generally, the high CPI 27‐33 ‐ket and low ACL 27‐33 ‐ket values indicated cold and dry climates such as for the Last Glacial Maximum (23.2–19.7k cal a bp ), Heinrich 1 event (17.6–15.6k cal a bp ) and Younger Dryas (12.8–11.6k cal a bp ), but low CPI 27‐33 ‐ket and high ACL 27‐33 ‐ket values denoted a warm and humid Holocene Climatic Optimum (7.0–4.3k cal a bp ). Therefore, n ‐alkan‐2‐ones have great paleoclimatic potential and can be applied together with other biomarkers to reconstruct a reliable paleoclimate record in lake sediments.

Cleaning chromium pollution in aquatic environments by bioremediation, photocatalytic remediation, electrochemical remediation and coupled remediation systems - Caiwen He; Lipeng Gu; Zhixiang Xu; Huan He; Gen Fu; Fengxia Han; Bin Huang; Xuejun Pan (Environmental Chemistry Letters, 2020)

Temporal and Spatial Dynamics of Astroglial Reaction and Immune Response in Cuprizone-Induced Demyelination - Jun An; Jun-Jun Yin; Yan He; Ruo-Xuan Sui; Qiang Miao; Qing Wang; Jie-Zhong Yu; Jing-Wen Yu; Fu-Dong Shi; Cun-Gen Ma; Bao-Guo Xiao (Neurotoxicity Research, 2020)

First report of tobacco rattle virus in hydrangea in China - Zhao-Lin Ji; Peng-Xiang Zhu; Gen-He He; Yong-Hui Liao; Feng Zhu (Journal of Plant Pathology, 2020)

Occurrence of chilli veinal mottle virus in Lycopersicon esculentum in Jiangxi Province in China - Yong-Hui Liao; Gen-He He; Zhao-Lin Ji; Feng Zhu (Journal of Plant Pathology, 2020)

Recent advances in amino acid sensing and new challenges for protein nutrition in aquaculture - Chengdong Liu; Xuan Wang; Huihui Zhou; Kangsen Mai; Gen He (Marine Life Science & Technology, 2019)

Establishment and characterization of a fibroblast-like cell line from the muscle of turbot (Scophthalmus maximus L.) - Ya Gao; Huihui Zhou; Zongyu Gao; Haowen Jiang; Xuan Wang; Kangsen Mai; Gen He (Fish Physiology and Biochemistry, 2019)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Two new species of Pustula (Albuginales, Oomycota) from Junggar Basin in China based on morphology and molecular data - Biao Xu; Young Joon Choi; Jia Ge Song; Shan He Zhang; Ping Gen Xi; Hyeon Dong Shin; Zi De Jiang (Mycological Progress, 2018)

Palatability of water-soluble extracts of protein sources and replacement of fishmeal by a selected mixture of protein sources for juvenile turbot (Scophthalmus maximus) - Chun Dong; Gen He; Kangsen Mai; Huihui Zhou; Wei Xu (Journal of Ocean University of China, 2016)

Expression pattern of peptide and amino acid genes in digestive tract of transporter juvenile turbot (Scophthalmus maximus L.) - Dandan Xu; Gen He; Kangsen Mai; Huihui Zhou; Wei Xu; Fei Song (Journal of Ocean University of China, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Lipoic acid protects dopaminergic neurons in LPS-induced Parkinson’s disease model - Yan-Hua Li; Qing He; Jie-zhong Yu; Chun-yun Liu; Ling Feng; Zhi Chai; Qing Wang; Hong-zhen Zhang; Guang-Xian Zhang; Bao-guo Xiao; Cun-gen Ma (Metabolic Brain Disease, 2015)

Effects of postprandial starvation on mRNA expression of endocrine-, amino acid and peptide transporter-, and metabolic enzyme-related genes in zebrafish (Danio rerio) - Juan Tian; Gen He; Kangsen Mai; Chengdong Liu (Fish Physiology and Biochemistry, 2015)

Effect of dietary lipid on the growth, fatty acid composition and Δ5 Fads expression of abalone (Haliotis discus hannai Ino) hepatopancreas - Mingzhu Li; Kangsen Mai; Qinghui Ai; Gen He; Wei Xu; Wenbing Zhang; Yanjiao Zhang; Huihui Zhou; Zhiguo Liufu (Journal of Ocean University of China, 2015)

Elevational patterns of endogenous hormones and their relation to resprouting ability of Quercus aquifolioides plants on the eastern edge of the Tibetan Plateau - Wan-Ze Zhu; San-Gen Wang; De-Zhen Yu; Yong Jiang; Mai-He Li (Trees, 2014)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

Target deletion of the AAA ATPase PpCDC48II in Physcomitrella patens results in freezing sensitivity after cold acclimation - Hui Wang; Shuo Jin; Xi Chen; XuKe Gen; YiKun He (Science China Life Sciences, 2012)

Degradation of fluoranthene by a newly isolated strain of Herbaspirillum chlorophenolicum from activated sludge - Hong X. Xu; Hai Y. Wu; Yu P. Qiu; Xiao Q. Shi; Gen H. He; Jing F. Zhang; Ji C. Wu (Biodegradation, 2011)

Genetic Diversity and Identity of Chinese Loquat Cultivars/Accessions (Eriobotrya japonica) Using Apple SSR Markers - Qiao He; Xiong Wei Li; Guo Lu Liang; Kun Ji; Qi Gao Guo; Wei Min Yuan; Gen Zhi Zhou; Kun Song Chen; W. Eric van de Weg; Zhong Shan Gao (Plant Molecular Biology Reporter, 2011)

Abnormal PMC microtubule distribution pattern and chromosome behavior resulted in low pollen fertility of an intersubspecific autotetraploid rice hybrid - Jin-Hua He; Muhammad Qasim Shahid; Zhi-Xiong Chen; Xing-An Chen; Xiang-Dong Liu; Yong-Gen Lu (Plant Systematics and Evolution, 2011)

Laboratory study of fluid viscosity induced ultrasonic velocity dispersion in reservoir sandstones - Tao He; Chang-Chun Zou; Fa-Gen Pei; Ke-Ying Ren; Fan-Da Kong; Ge Shi (Applied Geophysics, 2010)

Determinants of the geographical extent of invasive plants in China: effects of biogeographical origin, life cycle and time since introduction - Qiao Q. Huang; Chen Qian; Yu Wang; Xin Jia; Xin F. Dai; Hao Zhang; Fei He; Shao L. Peng; Gen X. Wang (Biodiversity and Conservation, 2010)

Fluid sensitivity study of elastic parameters in low-medium porosity and permeability reservoir rocks - Fa-Gen Pei; Chang-Chun Zou; Tao He; Ge Shi; Gen-Gen Qiu; Ke-Ying Ren (Applied Geophysics, 2010)

Occurrence of foliar rot of pak choy and Chinese mustard caused by Rhizoctonia solani AG1-IB in China - Gen-Hua Yang; Hai-Ru Chen; Shigeo Naito; Jian-Yu Wu; Xia-Hong He; Chun-Fang Duan (Journal of General Plant Pathology, 2005)

Gold Immunolocalization of Rubisco and Rubisco Activase in Pyrenoid of Chlamydomonas reinhardtii - Pei-Min He; Da-Bing Zhang; Geng-Yun Chen; Qi-Gen Liu; Wei-Ning Wu (Algae, 2003)

Web GIS: Implementation issues - Kou-gen Zheng; Soomro Tariq Rahim; Yun-he Pan (Chinese Geographical Science, 2000)